Why have children? [ the ethical debate - Overall, Christine , 1949- (Basic bioethics, 2012)
"In contemporary Western society, people are more often called upon to justify the choice not to have children than they are to supply reasons for having them. In this book, Christine Overall maintains that the burden of proof should be reversed: that the choice to have children calls for more careful justification and reasoning than the choice not to. Arguing that the choice to have children is not just a prudential or pragmatic decision but one with ethical repercussions, Overall offers a wide-ranging exploration of how we might think systematically and deeply about this fundamental aspect of human life."-- Jacket.